2010
DOI: 10.1590/s0102-695x2010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and acetylcholinesterase inhibitory activity of essential oils of Myrceugenia myrcioides(Cambess.) O. Berg and Eugenia riedelianaO. Berg, Myrtaceae

Abstract: ABSTRACT:The chemical composition of volatile oils from two Myrtaceae species, Myrceugenia myrcioides and Eugenia riedeliana, both native from the Brazilian Atlantic Rain Forest, was analyzed by GC-MS. Acetylcholinesterase inhibitory activity was colorimetrically evaluated for these oils. For M. myrcioides, monoterpene hydrocarbons represented the major class in the volatile oil, with α-pinene as the most abundant component and a weak inhibitory activity was observed, whilst for E. riedeliana sesquiterpenes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Essential oils are mixtures of many bioactive compounds whose occurrence are strongly dependent on wide range of factors ranging from plant species used [3] the part of the plant used [4] , the season the plant was harvested [5] , population differences of the same species [6] , or even between individuals of the same population [7] , [8] . Although the bio-inhibitory effect of an essential oil could be explained in terms of the individual effects or joint effects of some main constituents there is still little knowledge on the nature of interaction between these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Essential oils are mixtures of many bioactive compounds whose occurrence are strongly dependent on wide range of factors ranging from plant species used [3] the part of the plant used [4] , the season the plant was harvested [5] , population differences of the same species [6] , or even between individuals of the same population [7] , [8] . Although the bio-inhibitory effect of an essential oil could be explained in terms of the individual effects or joint effects of some main constituents there is still little knowledge on the nature of interaction between these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The IC 50 values were obtained for the hydroalcoholic extract, the essential oil, beta-asarone, and alpha-asarone and were 182.31 ± 16.78 µg/mL, 10.67 ± 0.81 µg/mL, 3.33 ± 0.02 µM, and 46.38 ± 2.69 µM, respectively. Souza et al [19] reported the AChE inhibitory activity of the essentials oils from Myrceugenia myrcioides (Cambess.) O. Berg and Eugenia riedeliana O. Berg.…”
Section: Cholinesterase Inhibitory Effect Of the Essential Oil MIXmentioning
confidence: 99%
“…(( E )-nerolidol, 24.6% and α-pinene, 24.0%) [ 27 ], E. verticillata (Vell.) Angely (valerianol, 28.1% and 10- epi -γ-eudesmol, 12.6%) [ 64 ], and E. xiriricana Mattos (spathulenol, 15.4% and β-pinene, 14.1%) [ 32 ]. In addition, three species presented other constituents such as esters, carboxylic acid, and oxygenated monoterpenes as main compounds.…”
Section: Volatile Profilesmentioning
confidence: 99%